Correction of the classification of a letter sent by Sharaf b. Shah-Muhammad to Sultan Mehmed Fatih in Ottoman Archives - أحمد دانیال صابر (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This study is about an attempt to correct the information about classifying an Ottoman document. It’s related to a letter sent to the Ottoman Sultan Mehmed Fatih by Sharaf b.Shah-Muhammed, the emir of bidlis. However, in classifying this letter an Ottoman archivist working for The Ottoman Archives of the Prime Minister’s Office has misclassified the document and added inaccurate information to the document. This misclassification may cause problems in understanding the contents of the document. So, it’s important to correct these errors. The following errors have been detected by the writer: the identity of the Bidlis prince, The data of the letter and the occasion about which the letter has been sent. This research has been facilitated due to writer’s familiarity with the vocabularies and frequently used Ottoman terms and last names. We have also used relevant Ottoman documents, academic papers, and studies in several languages covering the period of the letter. This study attempts to make a contribution to the historiography of the Kurds during the 15th century in the paper we should light on the early Ottoman and Kurdish relation and provides additional information in writing the history of Bidlis Principality.